THE EFFECT OF GUIDED WRITING TECHNIQUE AND ANXIETY UPON WRITING COMPETENCY - NT, Januartini,; PK, Nitiasih,; W, Suarnajaya, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This research aimed at investigating the effect of guided writing and anxiety upon writing competency. It was an experimental research with 2x2 factorial design. The result showed that (a) there was significant difference in writing competency between the students taught by guided writing technique and those taught by conventional technique, b) there was an interactional effect between the implementation of guided writing and the studentsâ anxiety, (c) there was significant different in the writing competency between the studentsâ with high anxiety, taught by implementing guided writing technique and those who are taught by conventional technique, (d) there was significant different in the writing competency between the studentsâ with low anxiety, taught by implementing guided writing technique and those who are taught by conventional technique, (e) the implementation of guided writing technique was responded in a more positive way by the students with high anxiety rather than by the ones with low anxiety. Â Keywords: guided writing, anxiety, and writing competency.